The Implementation of National Police Assesment Center in Encouraging Open Career Promotion - Albertus Recky Robertho; Asra’i Maros; Nanang Al Hidayat (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The competency of Indonesian National Police human resource is believed as the main factor in determining the successful of Indonesian National Police organization. Now, Indonesian National Police has been conducting an opening of career promotion program which one of the stages is use Assessment Center to examine managerial competencies. This research aims to analyze the policy and the impact of Assessment Center implementation in encouraging the opening of career promotion. The researcher used qualitative approach by applying observation, interview, and documents study as the data collecting techniques. The result of this research is the policy of implementing the Assessment Center in encouraging the opening of career promotion, in a narrow sense, has been done well although it hasn’t been done yet entirely. In a broad sense, the implementation of the Assessment Center in encouraging the opening of career promotion has not been succeed and have not had positive impact. This could happen for the Indonesian National Police as a bureaucracy organization, does not have the capacity of organization as the bureaucracy’s breadwinner, in which involves: organization structure; work mechanism; human resources;  financial support and needed resources. Those four elements are still not able to optimize the condition and encourage each other.